Quality of Life and Clinical Evaluation of Calcaneoplasty with a Balloon System for Calcaneal Fracture at 5 Years of Follow-Up - Giuseppe Maccagnano; Giovanni Noia; Giuseppe Danilo Cassano; Antonio Luciano Sarni; Raffaele Quitadamo; Costantino Stigliani; Francesco Liuzza; Raffaele Vitiello; Vito Pesce (Advances in Orthopedics)
Calcaneal fractures are a challenging clinical problem. Management of this type of injury remains controversial, especially in the context of intra-articular fractures. Surgical treatment with open reduction and internal synthesis (ORIF) is considered the standard treatment for CF, but it is associated with many complications. Several minimally invasive techniques such as balloon-assisted reduction, pin fixation, and tricalcium phosphate augmentation have been proposed to avoid the frequent and recurrent postoperative problems related to these fractures. We retrospectively examined 20 patients (mean age was 54.5), all undergoing minimally invasive calcaneoplasty surgery at our Department of Orthopaedics and Traumatology between 2012 and 2016. X-ray and CT scan were performed preoperatively and at 5 years of follow-up (57.9 ± 6 months). The American Orthopaedic Foot and Ankle Society (AOFAS) score was used for clinical examination, and the Short-Form (36) Health Survey (SF-36) score and Visual Analogue Scale (VAS) were used to assess the Health-Related Quality of Life (HRQoL). All 20 patients were available at the final follow-up. The mean AOFAS score was 82.25/100. The VAS results attest an overall average of 2.7/10 (0–9). The average of the parameters “Physical Health” and “Mental Health” was, respectively, 81.25 and 83.55. In terms of postoperative complications, we observed no cases of superficial or deep infections. Clinical response after balloon-assisted reduction, pin fixation, and tricalcium phosphate augmentation has shown a comparable or better outcome according to the AOFAS and VAS score. Quality-of-life scores, obtained according to the SF-36 questionnaire, are considered high. From both a clinical and quality-of-life point of view, our study highlights that there is not gender distinction. Further comparative studies with a higher number of patients are needed which assess the quality of life in the various techniques used to treat calcaneal fractures.